Structural, mechanical and electronic properties of two-dimensional chlorine-terminated transition metal carbides and nitrides. (3rd January 2020) - Qin, Yanqing; Zha, Xian-Hu; Bai, Xiaojing; Luo, Kan; Huang, Qing; Wang, Yi; Du, Shiyu
Abstract: Two-dimensional transition metal carbides and nitrides (MXenes) have attracted intensive attention since 2011, and surface groups have been determined to show a key role in MXene properties. Recently, an emerging functional group of chlorine was realized in MXenes, such as in Ti3 C2 Cl2 and Ti2 CCl2 . In order to understand and apply MXenes terminated by this type functional group, the structural, mechanical and electronic properties of M2 X2 Cl2 and M3 X2 Cl2 (M = Sc, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W; X = C, N) are investigated in this work from first-principles theory. For M2 X2 Cl2, the chlorine groups are all stabilized on the top-sites of the bottom M atoms on both sides. In M3 X2 Cl2, the surface groups of most configurations are functionalized on the top-sites of the middle M atoms. Regarding to the mechanical properties, the elastic constants vary significantly with the types of M and X elements. The highest Young modulus of 208.3 GPa is determined in Ta3 C2 Cl2 . The mechanical, dynamical and thermodynamic stabilities are further tested. Thirteen members.ie. M2 CCl2 (M = Sc, Ti, Zr, Nb, Hf), M2 NCl2 (M = Sc, Zr), M3 C2 Cl2 (M = Ti, Zr, Hf) and M3 N2 Cl2 (M = Sc, Ti, Zr) are determined to be stable. In addition, Ta2 CCl2, Hf2 NCl2, M3 C2 Cl2 (M = Sc, Nb, Ta) and Hf3 N2 Cl2 could be metestable. For these stable and metastable configurations, the electronic structures and work functions are studied. Most configurations are metallic, except for Sc2 CCl2, Zr3 N2 Cl2 and Hf3 N2 Cl2 . These three members are indirect band gap semiconductors, with their band gap values of 1.65, 0.135 and 0.246 eV, respectively. All the structures show high work functions, and the smallest value is approximate to 3.97 eV determined in Ti2 CCl2 . Our work implies that the chlorine-functionalized MXenes could be utilized in semiconductors and metallic films.